Thermal Comfort Analysis of Kecamatan Makasar District, Jakarta Timur Using Thermal Humidity Index (THI) - Ardiyansah, Ivan; H, Tricahyono N; Dahlia, Siti (Universitas Lambung Mangkurat, 2024)
Hot and humid climatic conditions significantly influence the quality of life in urban areas, particularly in tropical regions. Urbanization and climate change pose challenges to thermal comfort in Kecamatan Makasar, Jakarta Timur, a densely populated urban area. This study analyzes the thermal comfort levels in the area using temperature and humidity data from the Halim Perdanakusuma Meteorological Station for the period 2019–2023. The Thermal Humidity Index (THI) was calculated using the Nieuwolt equation to categorize thermal comfort levels. The results show variations in thermal comfort throughout the year, with the worst conditions in 2023 due to the El Niño phenomenon, while 2022 was more comfortable due to the influence of La Niña. This study highlights the need for adaptation strategies, such as implementing eco-friendly building designs, vertical urban farming, and planting shade trees like Taiwan Beuty, Kingkip, and Pacing, to enhance thermal comfort in Kecamatan Makasar.